2017
DOI: 10.1002/lno.10487
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community composition of particle‐associated and free‐living bacteria in mesopelagic and bathypelagic Southern Ocean water masses: Evidence of dispersal limitation in the Bransfield Strait

Abstract: The Southern Ocean constitutes about 10% of the global oceans' volume and is characterized by high primary production. Particulate organic matter (POM) is exported from the photic zone to the deep ocean and sustains life of particle associated (PA) and free-living (FL) bacterial communities in the dark realm. Little is known about the composition and diversity of PA and FL bacterial communities below the photic zone and how they differ among various regions of the Southern Ocean. Therefore, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 85 publications
(136 reference statements)
12
67
0
Order By: Relevance
“…The PA fraction is relatively enriched in members of γ-Proteobacteria, Verrucomicrobia, Bacteroidetes, Firmicutes and Planctomycetes (Azam and Malfatti, 2007;Milici et al, 2016;Salazar et al, 2016;Suter et al, 2018), while the FL assemblages are often populated by members of α-Proteobacteria (SAR11 clade or Ca. Pelagibacter) and Deferribacteres (DeLong et al, 1993;Crespo et al, 2013;Milici et al, 2017). However, significantly overlapped compositions of PA and FL microbial communities were also reported in a few studies (Hollibaugh et al, 2000;Ghiglione et al, 2007;Ortega-Retuerta et al, 2013;Rieck et al, 2015;Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The PA fraction is relatively enriched in members of γ-Proteobacteria, Verrucomicrobia, Bacteroidetes, Firmicutes and Planctomycetes (Azam and Malfatti, 2007;Milici et al, 2016;Salazar et al, 2016;Suter et al, 2018), while the FL assemblages are often populated by members of α-Proteobacteria (SAR11 clade or Ca. Pelagibacter) and Deferribacteres (DeLong et al, 1993;Crespo et al, 2013;Milici et al, 2017). However, significantly overlapped compositions of PA and FL microbial communities were also reported in a few studies (Hollibaugh et al, 2000;Ghiglione et al, 2007;Ortega-Retuerta et al, 2013;Rieck et al, 2015;Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 76%
“…4). Recent studies have shown that microbial populations in the meso-/ bathypelagic ocean are largely dissimilar to those of the epipelagic zone (Salazar et al, 2015;Milici et al, 2017;Liu et al, 2018a), indicative of a crucial environmental selection process exerted by depth.…”
Section: Environmental Factors Potentially Shaping Microbial Communitmentioning
confidence: 99%
See 1 more Smart Citation
“…Below the euphotic and 1% irradiance layers (aphotic, 150 to 5,125 m), the relative and absolute abundances of well-known mesopelagic bacterial clades, SAR324, SAR406, SAR202, Sulfitobacter, and the SVA0996 marine group, increased ( Fig. 3b and c) (20)(21)(22). In addition to the bacterial clades with high read abundances, there was also a large rare bacterial community throughout the SPG (relative read abundance of Ͻ0.1%).…”
mentioning
confidence: 98%
“…NS4 marine group bacteria within the phylum Bacteroidetes are commonly detected in marine microbial communities (Alonso et al 2007;Becker et al 2017;Milici et al 2017) and exhibit seasonality in some environments (Alonso-Saez et al 2015). Bacteria within the "Ca.…”
Section: Heterogeneity In Bacterial and Archaeal Diversity And Composmentioning
confidence: 99%